Ethnomedicines used in Trinidad and Tobago for urinary problems and diabetes mellitus - Lans, Cheryl A (BioMed Central, 2006)
BACKGROUND: This paper is based on ethnobotanical interviews conducted from 1996–2000 in Trinidad and Tobago with thirty male and female respondents. METHODS: A non-experimental validation was conducted on the plants used for urinary problems and diabetes mellitus: This is a preliminary step to establish that the plants used are safe or effective, to help direct clinical trials, and to inform Caribbean physicians of the plants' known properties to avoid counter-prescribing. RESULTS: The following plants are used to treat diabetes: Antigonon leptopus, Bidens alba, Bidens pilosa, Bixa orellana, Bontia daphnoides, Carica papaya, Catharanthus roseus, Cocos nucifera, Gomphrena globosa, Laportea aestuans, Momordica charantia, Morus alba, Phyllanthus urinaria and Spiranthes acaulis. Apium graviolens is used as a heart tonic and for low blood pressure. Bixa orellana, Bontia daphnoides, Cuscuta americana and Gomphrena globosa are used for jaundice. The following plants are used for hypertension: Aloe vera, Annona muricata, Artocarpus altilis, Bixa orellana, Bidens alba, Bidens pilosa, Bonta daphnoides, Carica papaya, Cecropia peltata, Citrus paradisi, Cola nitida, Crescentia cujete, Gomphrena globosa, Hibiscus sabdariffa, Kalanchoe pinnata, Morus alba, Nopalea cochinellifera, Ocimum campechianum, Passiflora quadrangularis, Persea americana and Tamarindus indicus. The plants used for kidney problems are Theobroma cacao, Chamaesyce hirta, Flemingia strobilifera, Peperomia rotundifolia, Petiveria alliacea, Nopalea cochinellifera, Apium graveolens, Cynodon dactylon, Eleusine indica, Gomphrena globosa, Pityrogramma calomelanos and Vetiveria zizanioides. Plants are also used for gall stones and for cooling. CONCLUSION: Chamaesyce hirta, Cissus verticillata, Kalanchoe pinnata, Peperomia spp., Portulaca oleraceae, Scoparia dulcis, and Zea mays have sufficient evidence to support their traditional use for urinary problems, "cooling" and high cholesterol. Eggplant extract as a hypocholesterolemic agent has some support but needs more study. The plants used for hypertension, jaundice and diabetes that may be safe and justify more formal evaluation are Annona squamosa, Aloe vera, Apium graveolens, Bidens alba, Carica papaya, Catharanthus roseus, Cecropia peltata, Citrus paradisi, Hibsicus sabdariffa, Momordica charantia, Morus alba, Persea americana, Phyllanthus urinaria, Tamarindus indicus and Tournefortia hirsutissima. Several of the plants are used for more than one condition and further trials should take this into account.